PERAN PEMERINTAH INDONESIA DALAM PERLINDUNGAN TENAGA KERJA WANITA PADA MASA PENEMPATAN - Annisa Nur Aini; Puji Astuti (Journal of Politic and Government Studies, 2019)
The sending of Indonesian workers abroad is an effort made by the Government of Indonesia to increase the country’s foreign exchange. In addition, with the presence of worker’s Remittances an important part of international capital flows, especially for labor exporters, this remittances has important meaning for development, because it can contribute 10% of the APBN value. Based on data obtained from the Development and Information Research Center (Puslitfo BNP2TKI), Malaysia is the main destination for sending Indonesian workers. But Malaysia has complex level of complicated problems for migrant workers in the informal sector because of the large number of cases of abuse, exploitation and threats of criminal penalties. This is what attract researcher to conduct research on the role of representatives of the Indonesian Government in providing protection for Indonesian Migrant Workers.This study aims to determine the factors that led to the case of Indonesian workers while working in Malaysia and also to analyze the role of representatives of the Indonesian Government in providing protection for Indonesian migrantworkers. This study uses a descriptive analysis type with qualitative approach. The main data are obtained from the interview process, observation and documentation.The result obtained in this study are found 3 factors that cause female workers to experience case of violence when working in the destination country that is due to lack of control from the government, low level of education and workers do not understand the contents of the employment contract agreement. In addition, after an analysis of the role of representatives of the Indonesian Government in providing protection for migrant workers, it was found that there were 3 efforts made in providing protection. Based on the findings above, there are several recommendation obtained, namely the Indonesian government must really suppress undocumented Indonesian migrant workers as an effort to reduce the spread of illegal Indonesian migrant workers, the cooperation between G-to-G between Indonesia and fellow labor-sending countries is needed.Keywords: Indonesian Migrant Workers, Social Welfare, Gender